"Guiding them to take responsibility": exploring UK speech and language therapists' views of supporting self-management of aphasia. Issue 4 (2nd April 2020) - Wray, Faye; Clarke, David; Forster, Anne
ABSTRACT: Background: Self-management approaches are increasingly recommended after stroke with the aim of supporting longer-term adaptation, adjustment and condition management. Stroke survivors with aphasia (SSWA) have particularly poor longer-term outcomes; however, the suitability of self-management for SSWA is unclear. Speech and language therapists (SLTs) play a key role in the provision of care for this group of stroke survivors; however, UK SLTs views of self-management have not been explored. Aims: To explore UK SLTs views of "self-management" as an approach in stroke rehabilitation including its application in practice with SSWA. Methods & Procedures: In depth, semi-structured qualitative interviews were conducted with SLTs from five NHS speech and language therapy services. Interview data were analysed using thematic analysis. Outcomes & Results: Eighteen SLTs participated in interviews. Many SLTs were not familiar with the term "self-management". However, SLTs were positive about the connotations of this term which aligned closely with the values they held about their role and the desired outcomes of rehabilitation. SLTs described multiple aspects of their existing practice which they associated with enabling "self-management" (e.g., self-directed practice of therapy tasks, encouraging SSWA to take responsibility for their own rehabilitation, involving family members in therapy). However, some SLTs identified difficulties involving SSWA as active participants in the rehabilitation process and in facilitating "readiness" to take responsibility for managing in the longer-term. Other barriers to enabling self-management were identified including limited session time for speech and language therapy in the community setting, difficulties involving family members in rehabilitation and a lack of access to other services to support self-management (including specialist psychological support). Conclusions: Making the transition to longer-term adaptation, adjustment and condition management is a complex and challenging task which is likely to require tailored support for many SSWA and their families. Supported self-management may help to facilitate this process; however, SLTs require a structured and clearly defined approach and training to assist implementation in practice. Organisational "buy-in" and support for self-management as a therapeutic approach within speech and language rehabilitation will also be required for successful implementation.